Crossbred progeny production performance in rural areas of Western Maharashtra - S B Gokhale; R L Bhagat (Journal of Livestock Biodiversity, 2025)
The network field progeny testing program sponsored by Indian Council of Agricultural Research (ICAR) is being operated in different parts of country and coordinated through Central Institute for Research on Cattle (CIRC), Meerut. Total 4,092 crossbred progeny (Holstein Friesian x Local) owned by 864 farmers spread over twenty six cattle breeding centres from Ahmednagar, Pune and Satara district of Western Maharashtra were reached to age at first calving (AFC) during the period of 20 years (1994 to 2013) and out of that 3,206 progeny completed their 1 lactation (2 died, 51 discontinued, 820 sold & 13 transferred). The performance of progeny was studied based on region (irrigated & unirrigated), participating units (BAIF, CIRC,GADVASU), sire dam’s milk yield (4500, 4501-5500, 5501-6500, 6501-7500 & >7501 kg), season of calving (rainy-June to September, winter-October to January, summer-February to May), age at first calving (<649, 650-938, 939-1208, 1209- 1478 & >1479 days) and progeny birth period (1994-97, 1998-01, 2002-05, 2006-09 & 2010-13). The 305 days milk yield was computed from the fortnightly milk yield records of alternate morning and evening milking. The first milk recording was got within fifteen days after calving and incomplete milk recording due to sale, transfer or death of progeny were excluded. The average first lactation 305 days milk yield of crossbred progeny under field conditions was recorded as 2974.95±12.03 kg and availability of irrigation facilities round the year, progeny calving season and birth period had significantly affected milk production levels of crossbred animals at field conditions.